Figure 26 from: Prous M, Liston A, Mutanen M (2021) Revision of the West Palaearctic Euura bergmanni and oligospila groups (Hymenoptera, Tenthredinidae). In: Proshchalykin MYu, Gokhman VE (Eds) Hymenoptera studies through space and time: A collection of papers dedicated to the 75th anniversary of Arkady S. Lelej. Journal of Hymenoptera Research 84: 187-269. https://doi.org/10.3897/jhr.84.68637 - Prous, Marko; Liston, Andrew; Mutanen, Marko (Zenodo, 2021)
Figure 26 Euura oligospila (A–C) and possible respondens (D–F) larvae from Salix fragilis (unconfirmed). A Finland 2018 Salix capreaB, C Sweden 2018 swept larva D Finland 2020 Salix fragilisE, F Finland 2020 Salix fragilis. Larva of respondens remain unconfirmed but adults of this species occurred at exactly the same spot as the larva D